MENINGKATAN KREATIVITAS ANAK MELALUI TEKNIK KOLASE - Nirwana Nirwana; Rani Tri Yulianti (Fakultas Keguruan dan Ilmu Penidikan UIM, 2020)
Abstract: Increasing Children's Creativity Through Collage Techniques. This study aims to increase children's creativity through collage techniques using garlic peels in children aged 4-5 years in Group A PAUD Melati Putih, Kel. Duri Pulo, Central Jakarta. This research is a classroom action research that follows the Hopkins model. This research includes 2 cycles where each cycle includes 4 stages, namely planning (planning), acting (implementing), observing (observation) and reflecting (reflection). The time of this research was in May 2019 and July 2019 with 12 children as research subjects, while to obtain actual information the data was collected through tests, interviews and observations. The results showed that the children's creativity had increased after being given a collage activity where the children were able to stick and arrange the garlic skin well according to the pattern. The use of garlic skin collage is also able to stimulate aspects of creativity including: fluency, flexibility, authenticity and detail in children.Keywords: children's creativity, collage technique